Apoptotic death of cortical neurons following surgical brain injury - Sulejczak, Dorota; Grieb, Paweł; Walski, Michał; Frontczak-Baniewicz, Małgorzata (Folia Neuropathologica, 2008)
Unilateral surgical brain injury of the rat is a model of surgery-related brain damage of humans. Our preliminary experiments showed two phenomena within the damaged cortical region of rat brain. Those were: degeneration and death of neurons and massive gliosis. In the present study we aimed to investigate the mechanisms of neuronal death following brain injury and to characterize responses of glial cells to the damage. We analyzed the morphological changes and alterations of immunochemical profile of cells localized in the brain areas adjacent to the lesion. Our data show the massive neuronal death following the lesion. Neurons undergo necrosis and apoptosis, but on the 4th day following the operation apoptosis prevails. Apoptotic cells showed heavy immunostaining for proapoptotic Bax and caspase 3. This result suggests the involvement of these proteins in neuronal apoptosis in our experimental model. Neuronal death is accompanied by the induction of astrogliosis in the perilesional cortical area. Astrocytes became hypertrophic. We did not detect any dying astrocytes at the investigated time point, but there is a possibility that apoptosis may occur in astroglia during another time period following the damage. This question requires further studies in our experimental model.